Stories for inclusive schools : developing young pupil's skills in assembly and in the classroom - Leicester, Mal (RoutledgeFalmer, 2004)
These fictional stories have been written to illustrate and help teachers overcome the wide range of differences in children and the issues they face that can make them feel excluded. All activities are suitable for the classroom or assembly hall.
Keywords: Inclusive education.; Storytelling.; Values -- Study and teaching (Elementary) -- Activity programs.; Mainstreaming in education.; Mainstreaming, Education; Intégration scolaire.; Art de conter.; EDUCATION -- Inclusive Education.; Mainstreaming in education; Inclusive education; Storytelling; Values -- Study and teaching (Elementary) -- Activity programs; Electronic books.